Mobile Learning to Improve Student Learning Outcomes in Tennis - Raibowo, Septian; Sugihartono, Tono; Permadi, Andes; Pujianto, Dian (Indonesian Journal of Physical Education and Sport Science, 2023)
Studi purpose. The purpose of this study was to improve the learning outcomes of physical education students in learning tennis Materials and Methods. The research method used was classroom action research using two cycles, namely cycle 1 and cycle 2. The method in this research was carried out by planning, implementing, observing, and reflecting on actions collaboratively to improve tennis learning outcomes. The subjects in this study were all seventh-semester students who took part in tennis lecture, totaling 35 students. This research was conducted from March 2023 to May 2023. The data obtained is then selected what is needed and can be used as a reference in compiling a research report. After getting an overview of the problems and constraints found in cycle 1, the next step is for researchers to rearrange the activity plan to get good results in the second cycle. Results. The results showed that in the first cycle the students’ completeness was 69%, and in the second cycle the students’ completeness was 94% Conclusions. The conclusion in this study is that the application of mobile learning-based learning can improve student learning outcomes in learning tennis.